Phytolith Production and Morphotypes in Modern Plants on the Tibetan Plateau - Ge, Yong; Jin, Yingshuai; Zhang, Xiaoling (Frontiers in Plant Science, 2022)
Tibetan Plateau is the "third pole" of Earth and significantly influences the world's ecosystems. However, limited work on phytolith analysis has been done due to its harsh environment, and no study on phytolith production and morphotypes in modern plants on the Tibetan Plateau has been carried out yet. In this study, we investigated 73 modern plant samples collected on the Tibetan Plateau to study phytolith production and morphology. The results showed that the major phytolith producers are Poaceae and Cyperaceae plants, the production of phytolith is higher than 0.4 million grains/g in most samples. We have found one new morphotype, BILOBATE SADDLE, which could be the diagnostic type for Tribe Stipeae. We also have found that phytoliths might indicate different humidity rather than the temperature on the Tibetan Plateau. Our findings add new information about phytoliths on the Tibetan Plateau and will aid the future phytolith analysis in this region.